2019
DOI: 10.1016/j.heliyon.2019.e01152
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic accumulation in lettuce (Lactuca sativa L.) and broad bean (Vicia faba L.) crops and its potential risk for human consumption

Abstract: Exposure to arsenic (As) is considered one of the primary health risks humans face worldwide. This study was conducted to determine As absorption by broad beans and lettuce crops grown in soil with As contents and irrigated with water contaminated with this toxic element, in Pastos Chicos, Jujuy (Argentina). Total dry biomass (TDB) and total As were determined in soils, roots, leaves, pods and seeds. These data were used to determine several parameters, such as translocation (TF) and bioconcentration (BCF) fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
2
6
1
1
Order By: Relevance
“…With increasing concentrations of As in the irrigation water, lettuce leaves had a lower water content, i.e., they became drier (Supplementary Figure 3). This is consistent with a previous study (Yanez et al, 2019) that observed that lettuce plant growth was significantly affected by irrigation with As-contaminated water (in terms of biomass reduction). However, there was no difference in plant mass between treatments, as also observed by Caporale et al (2014).…”
Section: Leafy Vegetablessupporting
confidence: 93%
See 1 more Smart Citation
“…With increasing concentrations of As in the irrigation water, lettuce leaves had a lower water content, i.e., they became drier (Supplementary Figure 3). This is consistent with a previous study (Yanez et al, 2019) that observed that lettuce plant growth was significantly affected by irrigation with As-contaminated water (in terms of biomass reduction). However, there was no difference in plant mass between treatments, as also observed by Caporale et al (2014).…”
Section: Leafy Vegetablessupporting
confidence: 93%
“…For lettuce leaves, the As content was higher than what was previously reported in the literature studies. However, the As content in the leaves of lettuce irrigated with 1,000 µg/L in this study was 0.7 times lower than one study carried out in Argentina (Yanez et al, 2019) using soil at 8 mg As/kg and As-contaminated water at 1,440 µg/L. There are several possible reasons explaining the higher levels of As observed in carrot and leafy vegetables: First, leafy vegetables have a greater capability to accumulate high levels of trace metals and minerals from soil than other vegetables (Jamali et al, 2008;Baig and Kazi, 2012).…”
Section: Accumulation Of As In the Edible Partscontrasting
confidence: 86%
“…The cumulative exposure to total cancer risk (TCR) of As, Cd and Pb was higher in children (1.36 × 10 −4 ) than in adults (7.83 × 10 −5 ) and the most important contribution would be As followed by Cd. Populations exposed to As from consumption of contaminated water and food could cause gastrointestinal diseases, cardiovascular and central nervous system disorders, and risk for several types of cancer (skin, lung, bladder, kidney) [ 106 , 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jamaica has high levels of As in soils [ 56 , 57 , 58 ] as well as surface water [ 17 ]. Since the ability to absorb As in soil and water differs between plants [ 58 , 59 , 60 ], the food safety of agricultural plants is of concern. In our pervious study, we reported that Jamaican children who ate avocado had a geometric mean blood As concentration of 4.78 μg/L, which is 10% higher than that among Jamaica children who did not eat such food ( p = 0.04) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our pervious study, we reported that Jamaican children who ate avocado had a geometric mean blood As concentration of 4.78 μg/L, which is 10% higher than that among Jamaica children who did not eat such food ( p = 0.04) [ 13 ]. In addition, Yañez et al have reported that broad beans accumulate As effectively and highlighted that when both the soil and the irrigation water contains high levels of As, eating broad beans could pose a greater risk of having a higher level of exposure to As [ 60 ]. All these studies support our results that the consumption of broad beans and avocado is directly associated with a detectable level of blood As concentrations in Jamaican children.…”
Section: Discussionmentioning
confidence: 99%